2014
DOI: 10.1007/8904_2014_303
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variability in Patients with Fanconi–Bickel Syndrome with Identical Mutations

Abstract: Objective: To describe the phenotypic features of an ethnically homogenous group of patients with Fanconi-Bickel syndrome harboring the p.R310X mutation.Methods: The study group consisted of eight patients from a single Bedouin family with clinically and molecularly diagnosed Fanconi-Bickel syndrome who had been followed at the same tertiary medical center for 8 years or more. All were homozygous for the p.R310X mutation. The medical files were reviewed for presenting signs and symptoms, laboratory and imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 21 publications
4
14
0
1
Order By: Relevance
“…This autosomal recessively inherited disease is caused by homozygous or compound heterozygous mutations in the SLC2A2 gene, mapped on chromosome 3q26.1-26.3, encoding the facultative glucose transporter 2 (GLUT2) [1]. While multiple mutations are described, there are few mutational hotspots and no genotype-phenotype correlation [2][3][4]. Variation in disease severity with identical mutations has also been reported [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This autosomal recessively inherited disease is caused by homozygous or compound heterozygous mutations in the SLC2A2 gene, mapped on chromosome 3q26.1-26.3, encoding the facultative glucose transporter 2 (GLUT2) [1]. While multiple mutations are described, there are few mutational hotspots and no genotype-phenotype correlation [2][3][4]. Variation in disease severity with identical mutations has also been reported [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…While multiple mutations are described, there are few mutational hotspots and no genotype-phenotype correlation [2][3][4]. Variation in disease severity with identical mutations has also been reported [2,5]. Patients typically present in infancy with vomiting, growth failure and refractory rickets [3].…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than one hundred Fanconi-Bickel syndrome patients and 59 or more mutations which are responsible for the syndrome have been reported. 5,6 Our patient has a novel mutation that was not described previously.…”
Section: Discussionmentioning
confidence: 74%
“…Molecular analysis of this patient resulted as GLUT2 compound heterozygosity in SCL2A2 and owing to this patient his sister was investigated with in first month of life and found same compound heterozygote mutation similarly to her brother. This disease has a broad spectrum of severity, Fridman et al 6 determined that a group of 8 patients have the same mutation and have different phenotypic expression and suggested that the broad spectrum of disease severity among these patients might be explained by modifier genes, as suggested for other monogenic diseases or unknown epigenetic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Ortak bulgularını boy kısalığı, taş bebek yüzü, kan şekerinde açlık ve tokluk durumunda belirginleşen dalgalanmalar, glukozüri ve proksimal tübülopatinin oluşturduğu sekiz olguyla yapılan bir çalışmada ortalama tanı yaşının 11 ay olduğu görülmektedir. Sekiz olgunun ikisinde yaşamın 1. ayında ortaya çıkan klinik bulgulara karşın tanı sırasıyla beş ay ve üç yaşta konulmuştur (5). Sekiz olgu ile yapılmış olan bir diğer çalışmada olguların tanı yaşının dört ay ile 16 yaş arasında değiştiği görülmektedir (6).…”
Section: Discussionunclassified